High Precision Precision Current Stabilizers with Induction Levitation Effect - Kerimzade G. S. (Institute for Research and Community Service (LPPM), Universitas Malikussaleh, Indonesia, 2023)
The present article discusses the characteristic features of the characteristics of precision controlled high-precision current stabilizers using the effect of induction levitation. The stability and shape of the load current determines the reliability, accuracy, efficiency, service life of automation devices, test equipment and electroplating baths. Determining the output characteristics, establishing analytical relationships between the initial data and the output parameters of the stabilizer is one of the stages of the algorithm for solving the problems of designing the parameters of an AC stabilizer with induction levitation of the moving part. This, in turn, contributes to the development of a mathematical model consisting of a system of equations of electric, magnetic, mechanical and thermal stabilizer circuits, the joint solution of which allows you to establish analytical relationships between the initial data and parameters such as working stroke, weight, winding and core sections, copper losses